Development of the Digital Financial Accounting I Learning Module in the Digital Nomad Era - Ni Luh Gede Erni Sulindawati; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2023)
This study aims to develop an effective and practical digital module for learning financial accounting I. The development uses the ADDIE model which consists of five stages which include analysis, design, development, implementation, and evaluation. The digital financial accounting learning module 1 developed contains an introduction, learning materials in the form of PPT, working papers in the form of Microsoft excel, summaries, practice questions and assessment rubrics. Based on the results of the evaluation of material experts and original media, the results of the digital media are valid and can be implemented. Digital module developed that can help facilitate students in understanding the material in learning financial accounting I.